CRP-Commissioned External Evaluation of the CGIAR Research Program on Dryland Cereals - Hillocks, Rory; Kumar, Ravinder; Martin, Adrienne; Robinson, Jonathan; Rothschild, George; Thangata, Paul (International Crops Research Institute for the Semi-Arid Tropics, 2016)
The evaluation is one of the five CRP commissioned evaluations requested by the CGIAR Fund Council, to assist and inform the planning and approval process for Phase II of the CRPs.